Enhancing Environmental Sustainability and Green Innovation in Vietnam: Does Foreign Aid Matter? - Bao, Mai Anh; Nguyet, Pham Thi Anh (International Journal of Energy Economics and Policy, 2025)
This study utilizes an extended time-varying autoregression model to examine contemporaneous and lagged linkages between environmental innovation and foreign aid in Vietnam from 1994 to 2022. The R2 decomposed linkage method is also employed as a robustness check. Our analysis reveals that, prior to 2015, environmental innovation drove foreign aid, facilitating key projects like solar power and waste management improvements. However, from 2015 onward, foreign aid began to overshadow environmental innovation, indicating a growing dependency on external support amidst slower domestic resource development. Furthermore, environmental innovation initially influenced economic growth but later became increasingly responsive to economic expansion. Environmental innovation’s interaction with CO2 emissions and HDI also evolved, showing its critical role in both environmental and human development. These findings suggest that effective policy should balance economic growth with sustained investment in environmental innovations to achieve long-term sustainability.